Production of Salted and Pressed Decapterus sp. and its Storage Characteristics - S.S., Gupta; R., Chakraborty (Fishery Technology, 2025)
A process for the production and storage of salted and pressed Decapterus sp. for human consumption was standardised. It involved immersion of the dressed fish in saturated sodium chloride brine for seven days followed by pressing in a wooden box under 0.064 kg cmÂ· 2 pressure for 15 h, packing in 200 gauge polythene bags and storage at ambient temperature. The product could be stored well for one month. Addition of 0.1 and 0.2% propionic acid to the curing brine increased the shelf life of the pressed product to 45 and 60 days, respectively by preventing growth of red halophiles and moulds.